Promising future of breast cancer vaccine asking for multidisciplinary collaboration: a literature review - Zhang, Zhanyi; Li, Mengyuan; Zhang, Lei; Wang, Maohua; Liu, Dequan; Tang, Shicong; Li, Yuhua; Fang, Xuedong; Ren, Shengnan (Frontiers in Cell and Developmental Biology, 2025)
Despite improved efficacy of breast cancer vaccine (BCV) made by multidisciplinary collaboration from fields such as materials science and computer science, clinical translation is still far from satisfactory. Herein, we reviewed the evolution trajectory of BCV and summarized the frontier topics and challenges for achieving successful clinical translation. Our analysis suggests that multi-omics and immunoinformatics are increasingly being used to expand target repertoires, and dedicated vaccine platforms are facilitating precise spatiotemporal co-delivery of epitopes and immune modulators. BCV has evolved towards precise delivery, strong immune properties, and combined therapy. Clinical translation requires the joint efforts of experts in clinical oncology, immunology, pharmacology, materials, and computer science.